Village Community Food Security through Development Plantation and Animal Husbandry Products in Menteng Karya Village, Kapuas Regency - Dhanu Pitoyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze that the empowerment of villagers can be obtained from the development of plantation and livestock products to increase self-reliance, there is a creative side to maintain food security for residents of Menteng Karya Village, Kapuas District, Central Kalimantan Province. The data were obtained based on the results of in-depth interviews from October to December 2020 with 5 UKM players and supported by secondary data from relevant sources. The data is processed based on the type of qualitative research. In the results of this study, it is found that SMEs have been able to develop products from their agricultural products, but encounter obstacles in the form of marketing, packaging, and licensing in the form of P-IRT and halal certification of the products they produce.